SISTEM PENERIMA BANTUAN RUMAH TIDAK LAYAK HUNI BERBASIS WEB DENGAN METODE WEIGHTED PRODUCT (Studi Kasus: Kantor Desa Cogreg) - Mohammad Arif; Sri Mulyati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
A livable house is an ideal container for a family in an urban or rural area that has been regulated in laws and government regulations regarding the administration and settlement areas. Based on research conducted by the author in Desa Cogreg, Parung, Bogor, the system for determining the recipients of uninhabitable housing assistance that exist has not run optimally, the condition of the village which has a population of 17,413 with an uneven level of economic capacity causes a large number of submissions for applications for uninhabitable housing. The decision-making system that is still running subjectively causes problems in the inspection process by the Inspectorate, which in the end finds houses that are not urgently to renovate, data collection management is also still done manually so that data documentation does not run effectively and efficiently. From the results of that research, the author designed a website-based application by applying the calculation using the weighted product method as a solution so that the determination of uninhabitable housing assistance in Desa Cogreg by the officials got the best results and made it easier to make decisions objectively, this website will make it easier for users to store data so that data can be obtained easily whenever needed, this website is also designed responsively so that it can be accessed in a compatible manner from any smart device.